Mabel Dodge Luhan new woman, new worlds - Rudnick, Lois Palken 1944- (Univ. of New Mexico Press, 1984)
This fascinating biography reveals a complex and talented woman who tried to influence the course of American history and in so doing captured the imaginations of writers and artists seeking to come to terms with their visions of the twentieth century. Luhan's life is the story of America's emergence from the Victorian age, and, in particular, the story of the conflicts that American women experienced in their struggle to become movers and shakers. Both as a woman and as a legend, Mabel Dodge Luhan embodies the cultural forces that have shaped modern America. - Back cover.